Kepemilikan Hak Kekayaan Intelektual dan Kinerja Sektor Ekonomi Kreatif di Indonesia - Ananda, Dzaki Yudi; Yudhistira, M. Halley (Jurnal Kebijakan Ekonomi, 2021)
Creative economy has been assigned as the backbone of Indonesian economy in the future. Based on Article 24 of the 2019 Law of Creative Economy, the protection of Intellectual Property Rights upholds an important role in creative economy. This research aims to observe the impact of intellectual property rights to the performance of creative economy as measured by the total income and export decision of creative economy actors, using the Ordinary Least Square (OLS) analytical method. It uses the cross-section data sourced from Badan Pusat Statistik (BPS)/Central Bureau of Statistics in 2016. This research concludes that the ownership of Intellectual Property Rights by economy actors has yielded significantly positive impact to the total income and export decision of creative economy actors.